Enhancement of perpendicularly magnetized τ-phase in Mn/Al bilayer thin films by swift heavy ion irradiation. (2023) - Khanduri, H.; Dimri, Mukesh C.; Kumar, Prashant; Link, J.; Stern, R.; Pant, R.P.
Abstract: This paper reports the swift heavy ion irradiation-induced tailoring of the structural and magnetic properties of the Mn/Al bilayer thin films. Mn/Al bilayer thin films were deposited on Si substrates by the evaporation technique, and as-deposited films were irradiated by a 100 MeV Ag ion beam with two distinct fluences. The molar fraction of τ- phase was enhanced at higher irradiation fluence, as revealed by the XRD and magnetic results. The average crystallite size was increased with the increase in irradiation fluence and obtained in a range of 11 to 14 nm. The magnetic hysteresis curves measured at 300 K confirmed the improvement in the ferromagnetic properties and the perpendicular magnetic anisotropy in these films. The enriched ferromagnetic properties were obtained in the perpendicular direction for the film irradiated at higher fluence, with the saturation magnetization ∼ 44 emu/cc, and coercivity ∼ 1590 Oe measured at the low temperature (5 K). These modified magnetic properties in Mn-Al alloy thin films are advantageous for their applications in spintronics and high-density magnetic memory devices.